2022
DOI: 10.3389/fnut.2022.1044895
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to an erythropoiesis-stimulating agent is correlated with body composition in patients undergoing chronic hemodialysis

Abstract: BackgroundResistance to erythropoiesis-stimulating agents (ESA) is associated with adverse outcomes in patients undergoing chronic hemodialysis. However, the impact of body composition on ESA response remains uncertain. This study retrospectively investigated whether there is an association between the ESA resistance index (ERI) and body composition in patients undergoing chronic hemodialysis.MethodsMultifrequency bioelectrical impedance analysis was used to measure body composition every six months. The ERI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have reported that ESA resistance is associated not only with higher risk of cardiovascular events and mortality but also with lower SMM in haemodialysis patients. [8][9][10]55,56 In addition, increased risk of mortality associated with ESA resistance has been shown to be related to higher doses of ESAs and known underlying causes of ESA resistance such as inadequate haemodialysis, nutritional deficiencies, chronic inflammation, and bone marrow disorders. [57][58][59] Iron deficiency is associated with lower SMM and function in community-dwelling individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have reported that ESA resistance is associated not only with higher risk of cardiovascular events and mortality but also with lower SMM in haemodialysis patients. [8][9][10]55,56 In addition, increased risk of mortality associated with ESA resistance has been shown to be related to higher doses of ESAs and known underlying causes of ESA resistance such as inadequate haemodialysis, nutritional deficiencies, chronic inflammation, and bone marrow disorders. [57][58][59] Iron deficiency is associated with lower SMM and function in community-dwelling individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of HIF‐PHI users in this study displayed hyporesponsiveness to ESAs, given that they needed the switches from ESAs to HIF‐PHIs when the dose of ESAs was at least 30 μg of darbepoetin equivalent per week. Recent studies have reported that ESA resistance is associated not only with higher risk of cardiovascular events and mortality but also with lower SMM in haemodialysis patients 8–10,55,56 . In addition, increased risk of mortality associated with ESA resistance has been shown to be related to higher doses of ESAs and known underlying causes of ESA resistance such as inadequate haemodialysis, nutritional deficiencies, chronic inflammation, and bone marrow disorders 57–59 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…González-Ortiz et al showed a positive association between protein–energy wasting and ERI in HD patients [ 27 ]. Other studies have shown that the geriatric nutritional risk index, body composition, and sex are associated with ERI in HD patients [ 28 , 29 , 30 ]. Comorbidities have variable effects on the responsiveness of ESA, which are mediated through the inflammatory response and leads to increases in ERI [ 30 ].…”
Section: Discussionmentioning
confidence: 99%